2020
DOI: 10.1002/ppsc.202000054
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Boron in Mesoporous Bioactive Glass Nanoparticles Reduces Inflammatory Response and Delays Osteogenic Differentiation

Abstract: Mesoporous bioactive glass nanoparticles (MBG) are multifunctional building blocks for tissue regeneration and nanomedicine applications. Incorporation of biologically active ions can endow MBG with additional functionalities toward promoted therapeutic effects. Here, boron is incorporated into MBG by using a sol–gel approach. The concentration of boron incorporated is controllable by tuning the amount of boron precursor. Two types of boron‐doped MBG, namely 10B‐ and 15B‐MBG (5.8 and 6.5 mol% of B2O3, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…The new diffraction signals of the XRD pattern ( Figure 6 b) were detected at approximate by 2θ = 26.0°, 31.7°, 32.1°, 32.9°, and 49.4°, which correspond to hydroxyapatite (JCPD 09-0432) [ 80 ]. Besides, with the observation of surface morphology ( Figure 6 c), needle-like structures were seen to be present on the surface of PHBV/MBGN/CIN20 microspheres, which exhibit the characteristic morphology of HA formed on MBGN after immersing in SBF [ 70 , 81 ]. Further verification of the presence of HA was performed by EDS analysis ( Figure 6 d).…”
Section: Resultsmentioning
confidence: 99%
“…The new diffraction signals of the XRD pattern ( Figure 6 b) were detected at approximate by 2θ = 26.0°, 31.7°, 32.1°, 32.9°, and 49.4°, which correspond to hydroxyapatite (JCPD 09-0432) [ 80 ]. Besides, with the observation of surface morphology ( Figure 6 c), needle-like structures were seen to be present on the surface of PHBV/MBGN/CIN20 microspheres, which exhibit the characteristic morphology of HA formed on MBGN after immersing in SBF [ 70 , 81 ]. Further verification of the presence of HA was performed by EDS analysis ( Figure 6 d).…”
Section: Resultsmentioning
confidence: 99%
“…There are reports in the literature on the fabrication of B-doped bioactive glass nanoparticles [ 49 , 50 ], but, to the best of our knowledge, there are very limited data available on the fabrication and characterization of Co-doped B-containing bioactive glass nanoparticles. Rad et al reported that the content of B in their B-doped bioactive glass nanoparticles, prepared using an acid-base catalyzed sol-gel method, was quite similar to their designed compositions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 MBGNs can be doped with several metallic ions to provide a therapeutic effect. 15,16 For example, Westhauser et al 17 and Nawaz et al 18 doped MBGNs (composition in mol.%: 50 SiO 2 -10 P2O 5 -40 Cao) with Mn (composition in mol.%: 50 SiO 2 -10 P2O 5 -35 Cao-5 MnO). The results have shown that the 5 mol.% addition of MnO in the MBGNs supported osteogenic differentiation and enhanced the upregulation of genes encoding for extracellular matrix proteins.…”
Section: Introductionmentioning
confidence: 99%
“…MBGNs based on SiO 2 –P2O 5 –Cao have demonstrated promising properties for the local delivery of therapeutically active ions 13,14 . MBGNs can be doped with several metallic ions to provide a therapeutic effect 15,16 . For example, Westhauser et al 17 and Nawaz et al 18 doped MBGNs (composition in mol.%: 50 SiO 2 –10 P2O 5 –40 Cao) with Mn (composition in mol.%: 50 SiO 2 –10 P2O 5 –35 Cao–5 MnO).…”
Section: Introductionmentioning
confidence: 99%